Understanding variations in pediatric asthma care processes in the emergency department using visual analytics. (5th February 2015) - Basole, Rahul C.; Braunstein, Mark L.; Kumar, Vikas; Park, Hyunwoo; Kahng, Minsuk; Chau, Duen Horng (Polo); Tamersoy, Acar; Hirsh, Daniel A.; Serban, Nicoleta; Bost, James; Lesnick, Burton; Schissel, Beth L.; et al.
Abstract: Health care delivery processes consist of complex activity sequences spanning organizational, spatial, and temporal boundaries. Care is human-directed so these processes can have wide variations in cost, quality, and outcome making systemic care process analysis, conformance testing, and improvement challenging. We designed and developed an interactive visual analytic process exploration and discovery tool and used it to explore clinical data from 5784 pediatric asthma emergency department patients.